Perennial Dicot Weed Species that Occur in Bean (Phaseolus Vulgaris) Fields and Cause Damage - Muminovna, Turdieva Nilufar; Jumanazar qizi, Raimiova Feruza (American Journal of Biodiversity, 2026)
This work analyzes perennial dicotyledonous weed species found in bean (Phaseolus vulgaris) fields and their negative impact on crop productivity. The study examines the biological characteristics, distribution conditions, and effects on bean growth of major weed species such as field bindweed, creeping thistle, broad-leaved dock, hoary cress, spiny caper, and common vetch.